PENGARUH KARAKTERISTIK TUJUAN ANGGARAN, LINGKUNGAN BIROKRASI, KOMITMEN MANAJEMEN, DAN KUALITAS SUMBER DAYA MANUSIA TERHADAP PENYERAPAN ANGGARAN - Denita Lilik Mastuti, Suharno & Djoko Kristianto (Universitas Slamet Riyadi, 2017)
The purpose of this study is to analyze the influence of characteristics ofbudget objectives, bureaucratic environment, management commitment and humanresource quality to budget absorption. Type of survey research in sub-district inBanjarsari Sub-district Surakarta City. The population of employee research isdirectly related to the preparation of the budget of 46 people, all of which are usedas research samples with census techniques. Data collection techniques useddocumentation and questionnaires. Data analysis techniques use multiple linearregression. The results showed that the characteristics of budget objectives,bureaucracy environment, management commitment and quality of human resourceshave a positive and significant effect on the absorption of urban budget inKecamatan Banjarsari Kota Surakarta.Keywords: characteristics of budget objectives, bureaucratic environment,management commitment, human resources quality